Análisis jurídico del impuesto a la renta de quinta categoría en trabajadores dependientes en Loreto, 2019 - Sosa Verano, Christian Manuel (2022)
The fifth category income tax is applied to dependent workers such as administrators, accountants, assistants, nurses, obstetricians, doctors, workers, people with complete secondary school, complete primary school, among others, from whom the gross income tax is withheld, without applying the deduction of expenses and costs as applied to third category income. The objective of the investigation is to show inequalities the violation of the principle of taxable capacity, noting that dependents are withheld the tax from a gross income of S/. 2,150.00; considering the state that with said sum, the worker is able to cover his essential needs of education, clothing, housing, health, food, recreation and additionally to pay fifth category rent. However, businessmen pay the income tax of the third category of the utility, the same that is determined from the income minus all the expenses, taxing on the utility, on what is left over, on what remains, after having deducted all Expenses. Currently the rental of property, accommodation services, food with electronic receipt is deducted, understanding that most of the family expenditure is food that comes from markets and that it should be deducted in its entirety for the family well-being.